Strengthening the Key Features of Volumizing Fillers: Projection Capacity and Long-Term Persistence - Killian Flégeau; Jing Jing; Camille Vantou; Romain Brusini; François Bourdon; Jimmy Faivre (MDPI AG, 2023)
Volumizing fillers aim to create or restore facial volume in fat layers. To provide strong tissue lifting and long-term persistence, gels are generally designed with stiff properties, characterized by a high storage modulus (G'). However, clinical evidence shows a discrepancy between high G' and good lifting capacities, especially after skin tension has been exerted on the gel. To better explore the in vivo behavior of a gel, we first evaluated the elastic moduli of five commercial volumizers (RHA4, JUVVOL, RESVOL, RESLYFT, and BELVOL) in dynamic compression mode, E'. We further developed a Projection Index score based on the rheological assessment of creep in compression to mimic skin tension-induced stress relaxation (flattening). Finally, the ability of a gel to resist enzymatic degradation was analyzed with a multidose approach. Despite similar clinical indications, volumizers exhibited distinct behaviors. RHA4 and BELVOL showed the highest E' values (resistance to strain), RHA4, JUVVOL, and RESVOL exhibited the greatest projection capacities, while JUVVOL and RHA4 offered the largest persistence to enzymatic degradation. In this article, we introduce the use of the Projection Index to efficiently assess the ability of a gel to lift tissues, thus increasing preclinical models' efficiency and reducing the need for animal studies.